THE EFFECT OF THE IMPLEMENTATION OF SERVICE MANAGEMENT FUNCTIONS ON NURSES’ PERFORMANCE AT BINJAI ARMY HOSPITAL - Nadhifa, Sayra; Nuraini, Nuraini; Yuniati, Yuniati (HEARTY, 2026)
The increasing demand for high-quality hospital services requires the effective implementation of service management functions to support nurses’ performance as primary healthcare providers. Nurses’ performance is a key indicator of hospital service success, as it directly influences the quality of care delivered. Therefore, this study aims to analyze the effect of hospital service management implementation on nurses’ performance as a basis for improving service quality. This study employed a quantitative method with a cross-sectional design conducted from August 2025 to February 2026. The sample consisted of all nurses at Binjai Army Hospital, totaling 100 respondents. Data were analyzed using the Chi-square test and logistic regression. The results showed that most respondents rated planning (59%), organizing (60%), implementation (63%), and controlling (60%) as good, with an overall satisfaction level of 59%. Bivariate analysis indicated that all service management variables (planning, organizing, implementation, and controlling) had a significant effect on patient satisfaction (p < 0.05), with implementation identified as the most dominant factor. In conclusion, the implementation of hospital service management functions—planning, organizing, implementation, and controlling—significantly affects nurses’ performance at Binjai Army Hospital. It is recommended that hospital management strengthen service management systems through the development of clear standard operating procedures, improved work coordination, routine supervision, and periodic evaluation to sustainably enhance nurses’ performance.